Representações sociais de professoras e professores que ensinam matemática sobre o fenômeno da deficiência - Moreira, Geraldo Eustáquio (2012)
The present Thesis is integrated, epistemologically, in the sphere of Mathematics Education and Special Needs Education in general and, in more restricted terms, it is grounded in social representations of teachers that teach Mathematics on the disability phenomenon. The objective was to identify, analyze and present the social representations of 55 female teachers and 10 male teachers, from four public schools of São Paulo, about the disability phenomenon, as well as to know their knowledge, opinions and doubts on the theme. The data collection took place in three different daily situations, all experienced in Mathematics classes, used as thematic triggers, in order to arouse in the interviewee the willingness to express him or herself on the disability theme. In the first story, we aimed to understand how the interviewees felt facing a friendship situation between two adolescents, having one of them a disability; in the second situation, after encountering an explicit circumstance of prejudice, we sought to verify the interviewees opinions, attitudes and behavior and, in the last story, we exposed the declarant to a situation that aimed to identify the concepts he or she has on the disability phenomenon. We used the Collective Subject Speech methodology, having as a theoretical and methodological referential the Social Representation Theory. The results highlight, on one hand, the presence of distinct social representations on the theme, with anchored postures not only on the support and encouragement of the inclusion of the student with disability, but, also on the other hand, on the representations anchored on the manifestations of doubt, opinions and attitudes opposed to the philosophy of inclusion